Atorvastatin combined with low-dose dexamethasone improves the neuroinflammation and survival in mice with intracerebral hemorrhage - Song, Yiming; Liu, Xuanhui; Yuan, Jiangyuan; Sha, Zhuang; Jiang, Weiwei; Liu, Mingqi; Qian, Yu; Gao, Chuang; Gong, Zhitao; Luo, Hongliang; Zhou, Xin; Huang, Jinhao; et al. (Frontiers in Neuroscience, 2022)
Intracerebral hemorrhage (ICH) is a fatal disease with high mortality and poor prognosis that triggers multiple severe brain injuries associated with an inflammatory cascade response that cannot be treated with any effective medication. Atorvastatin (ATO) suppresses inflammation, alleviates brain trauma, and eliminates subdural hematoma. Dexamethasone (DXM) also has the capacity to inhibit inflammation. Thus, we combined ATO with low-dose DXM to treat ICH mice in vivo to examine whether the combined treatment can inhibit secondary inflammation around the cerebral hemorrhage and decrease overall mortality. Compared to the monotherapy by either ATO or DXM, the combined treatment significantly improves the survivorship of the ICH mice, accelerates their recovery of impaired neurological function, and modulates the circulating cytokines, oxidative products, and apoptosis. Moreover, the benefit of ATO-DXM combination therapy was most pronounced on day 3 after dosing compared to ATO or DXM alone. Thus, early administration of ATO combined with low-dose-DXM promotes better survival of ICH and improves neurological function by reducing neuroinflammation and brain edema in their early phase.